Factors influencing smallholder cardava banana farmers’ participation in collective marketing in Southern Philippines (Asian Journal of Agriculture, 2022)
Abstract. Orejudos RD, Duka JU, Baladjay AA. 2022. Factors influencing smallholder cardava banana farmers' participation in collective marketing in Southern Philippines. Asian J Agric 6: 87-96. Cardava banana farming is a good source of living for smallholder rural farmers in Cotabato province in the Southern Philippines, but they are often faced with constraints in finding the right buyers and good prices. This research examined the factors influencing smallholder cardava banana farmers' participation in collective marketing in the Southern Philippines. The data from 172 respondents were gathered using a pre-tested survey questionnaire. Means, Percentages, and linear regression analysis were used to address the study's objectives. The study results established that smallholder cardava banana farmers' participation in collective marketing is predominantly determined by household size, price, and payment scheme. In addition, they are also determined by the delivery schedule, distance to the market, access to extension services, access to production inputs, access to credit assistance, access to market information, and membership in farmers' organizations. This study's findings offer empirical evidence that socio-economic, market,- and institutional factors can influence the participation of smallholder cardava banana farmers in collective marketing.
Keywords: Group marketing, institutional market, linkSfarM project, market participation, poverty alleviation